Grain Coarsening of Columnar Iron Polycrystals by Repetitive Cold Work and Annealing - Holzer, Jakub; Husťák, Miroslav; Hegrová, Jitka; Gröger, Roman (Metallurgical and materials transactions. A, Physical metallurgy and materials science, 2023)
Experimental studies on single crystals of pure metals are essential for understanding the mechanisms governing their plastic deformation as well as for interpretations of these observations using theoretical and atomistic models. Iron is especially interesting, because its low-temperature plastic response may be affected by ferromagnetism. However, the growth of large single crystals of iron from the melt is notoriously difficult due to the allotropic transformation between its face-centered and body-centered cubic phases. An alternative route is to start with polycrystalline iron of high purity and subject it to one or more cycles of cold work and subsequent annealing. This process is demonstrated here by utilizing 99.99 pct pure polycrystalline electrolytic iron with initially strong columnar microstructure. We investigate how the final grain size depends on the number of cold work cycles, annealing time in vacuum, and annealing temperature. The size distribution and characters of individual grains are assessed on etched samples using the electron backscatter diffraction analysis. The largest grains obtained by this process have the characteristic sizes above 2 mm and require four cycles of cold work, each followed by annealing at 870 °C for 8 hours. The probability density of grain sizes after optimal combination of cold work and annealing is well approximated by log-normal distribution. These results constitute guidelines to optimal processing of columnar polycrystals for further extraction of single-crystalline samples.